Penerapan Aplikasi Kahoot dalam Meningkatkan Hasil Belajar Peserta Didik - dermawan, Rendi; Masito Mutiara, Tyas; Kurnisar, Kurnisar (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2023)
The purpose of this study was to determine the increase in student learning outcomes using the Kahoot application in class XI IPS 1 SMA Negeri 3 Palembang. The research method used was classroom action research (CAR) with a sample size of 35. The data collection method used tests to obtain learning outcomes in the pre-cycle with an average grade of 65.4, then cycle I with an average grade of 73.5 , and cycle II with an average value of 85.6 which experienced an increase. It can be concluded that the application of the Kahoot application can improve the learning outcomes of students in class XI IPS 1 SMA Negeri 3 Palembang.